2009
DOI: 10.1080/09540120902883119
|View full text |Cite
|
Sign up to set email alerts
|

Voices on adherence to ART in Ethiopia and Uganda: a matter of choice or simply not an option?

Abstract: This paper explores HIV patients' adherence to antiretroviral treatment (ART) in resource-limited contexts in Uganda and Ethiopia, where ART is provided free of charge. Qualitative semi-structured interviews were conducted with 79 patients, 17 peer counselors, and 22 providers in ART facilities in urban and rural areas of Ethiopia and Uganda. Interviewees voiced their experiences of, and views on ART adherence both from an individual and a system level perspective. Two main themes emerged from the content anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 20 publications
2
51
1
Order By: Relevance
“…Regular attendance to pre-ARV care enhances routine clinical assessment of a patient's eligibility for treatment and hence timely ART initiation. Non-adherence to pre-ARV care or loss to follow-up could be due to inadequate or poor quality post-test counseling, late disease presentation, long waiting times, lack of incentives to motivate the PLHIV to come for care in time or deterrent actions by other providers, such as traditional and spiritual healers [10,25,30,[34][35][36][37] Corresponds to L 18 by reviewer 2.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Regular attendance to pre-ARV care enhances routine clinical assessment of a patient's eligibility for treatment and hence timely ART initiation. Non-adherence to pre-ARV care or loss to follow-up could be due to inadequate or poor quality post-test counseling, late disease presentation, long waiting times, lack of incentives to motivate the PLHIV to come for care in time or deterrent actions by other providers, such as traditional and spiritual healers [10,25,30,[34][35][36][37] Corresponds to L 18 by reviewer 2.…”
Section: Discussionmentioning
confidence: 96%
“…A recent qualitative study on adherence to ART in Uganda found that clients' competing costs and trust in ART, system resource constraints and the quality of counseling were vital factors influencing adherence [30]. We hypothesized that the reasons for late ART initiation differed from those influencing adherence to ART once already initiated on treatment and the policy implications/challenges would therefore also be different.…”
Section: Introductionmentioning
confidence: 93%
“…We showed that both individual-level and system-level barriers can affect appointment keeping and adherence to medications in East Africa, and this ultimately compromises optimal clinical outcomes (Gusdal et al 2009). For practical reasons, INRUD-IAA focused on developing affordable system-level interventions that target both systems-related and individual barriers to adherence (see Figure 1).…”
Section: Theory Of Changementioning
confidence: 99%
“…In our previous work in the International Network for the Rational Use of Drugs Initiative on Antiretroviral Adherence (INRUD-IAA), we used both quantitative and qualitative methods to explore the prevalence and determinants of adherence and appointment keeping in five East African countries (Gusdal et al 2009;Chalker et al 2010;Ross-Degnan et al 2010). We showed that both individual-level and system-level barriers can affect appointment keeping and adherence to medications in East Africa, and this ultimately compromises optimal clinical outcomes (Gusdal et al 2009).…”
Section: Theory Of Changementioning
confidence: 99%
See 1 more Smart Citation